Amorphous nanostructured FeOOH and Co–Ni double hydroxides for high-performance aqueous asymmetric supercapacitors. (March 2016) - Chen, Jizhang; Xu, Junling; Zhou, Shuang; Zhao, Ni; Wong, Ching-Ping
Abstract: Amorphous fish-scale-like FeOOH and flower-like Co–Ni double hydroxides (Co–Ni-DH) have been synthesized through one-step electrodeposition. The unique nanostructures of the hydroxides provide a large number of surface active sites, while the amorphous nature of the material systems facilitates the diffusion and reaction of electrolyte ions and enables an isotropic charging/discharging process. Because of these advantages, the FeOOH and Co–Ni-DH electrodes exhibit high pseudocapacitances of 1.11 F cm −2 /867 F g −1 and 1.48 F cm −2 /1201 F g −1, respectively. In addition, high rate capabilities and superior cyclabilities are achieved. By using the FeOOH and Co–Ni-DH as the anode and cathode, respectively, we have assembled an aqueous asymmetric supercapacitor that delivers a high energy density of 86.4 W h kg −1 /0.723 mW h cm −3 and a high power density of 11.6 kW kg −1 /0.973 mW cm −3 . Moreover, the fabrication process presented in this work is facile, scalable, cost-effective, and environmentally benign, offering a feasible solution for manufacturing next-generation high-performance energy storage devices. Graphical abstract: Highlights: Amorphous nanostructured fishscale-like FeOOH is deposited on the Ni foam. Amorphous flower-like Co–Ni double hydroxides are grown on the Ni foam. The fabrication process is facile, scalable, and cost-effective. The FeOOH and Co–Ni double hydroxides show great pseudocapacitive performances. The asymmetric supercapacitor delivers high energy and power densities.